No one is old here! Uses and interpretations of services provided by a Senior Activity Center in a low-income urban district of Peru - Ramos Bonilla, Gabriela (2016)
The article analyzes the uses and interpretations of the services of a Senior Activity Center program (Centros del Adulto Mayor - CAM) by its users and the professionals who direct it in a low-income urban district of Lima, Peru. Based on ethnographic research, and revealed the way a public policy builds an «ideal old age» which is promoted by their services. This is not passively assumed by the professionals who implement the program locally. They reinterpret their guidelines based on their common sense and experience which generates contradictions and a partial reproduction of prejudices related to old age. On the other hand, users use the program as a mechanism to deal with moments of crisis that were experienced at this stage of their lives. Also to oppose the hegemonic discourse of old age that doesn’t satisfy them. The CAM offers these opportunities but they don’t benefit all members uniformly because they don’t have the same resources or capacity. The program also creates discomfort between these elders because it isolates them conceptually and spatially when it calls them «seniors».